2021
DOI: 10.1371/journal.pone.0255028
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the prevalence of malaria associated with pregnancy in Colombia 2000–2020

Abstract: Knowledge about malaria associated with pregnancy is scarce in Latin America, and in Colombia, little is known about the magnitude of this infection. A systematic review was conducted to determine the prevalence of malaria associated with pregnancy (MAP) and each of its three forms: gestational (GM), placental (PM), and congenital (CM) tested using thick blood smear (TBS) and PCR. Also to compare the proportion of cases due to Plasmodium falciparum and Plasmodium vivax in Colombia from the year 2000–2020. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 27 publications
(33 reference statements)
4
18
0
6
Order By: Relevance
“…In the specific case of Colombia, previous studies have reported frequencies of GM ranging from 10.4% with TBS to 32% with qPCR 12 , 20 , 21 . In a meta-analysis of the prevalence of malaria associated with pregnancy in Colombia 2000–2020 the prevalence of GM was 5.8% (95% CI 3.8–8.7) by TBS, 16.7% (95% CI 9.0–28.8) with PCR, and 8.5% (95% CI 3.4–19.7) of submicroscopic infections; with a high heterogeneity in the magnitude of the infection, attributable to the level of endemicity of the different regions studied, and variations in the study designs 30 . The high frequency reported in different populations, shown the high gynecological-obstetric risk attributable to GM, and it indirectly demonstrates problems in the control of the infections in prenatal care programs.…”
Section: Discussionmentioning
confidence: 96%
“…In the specific case of Colombia, previous studies have reported frequencies of GM ranging from 10.4% with TBS to 32% with qPCR 12 , 20 , 21 . In a meta-analysis of the prevalence of malaria associated with pregnancy in Colombia 2000–2020 the prevalence of GM was 5.8% (95% CI 3.8–8.7) by TBS, 16.7% (95% CI 9.0–28.8) with PCR, and 8.5% (95% CI 3.4–19.7) of submicroscopic infections; with a high heterogeneity in the magnitude of the infection, attributable to the level of endemicity of the different regions studied, and variations in the study designs 30 . The high frequency reported in different populations, shown the high gynecological-obstetric risk attributable to GM, and it indirectly demonstrates problems in the control of the infections in prenatal care programs.…”
Section: Discussionmentioning
confidence: 96%
“…No se presentan resultados metaanalíticos de evaluación diagnóstica para malaria placentaria y congénita dado el número insuficiente de estudios para estimar una medida combinada. A pesar de esto, los pocos datos disponibles muestran grandes deficiencias de la GG para estas dos formas clínicas de la malaria, incluso en la forma congénita se halla sensibilidad de 0% (17) , lo que concuerda con un metaanálisis de los estudios colombianos en el cual la frecuencia de malaria congénita con GG fue 1% mientras que al usar PCR fue 16% (10) . En el caso de la malaria placentaria es importante resaltar que la capacidad de detectar casos con GG fue muy baja en comparación con PCR, lo que es preocupante dado que en esta presentación clínica el estándar diagnóstico es la histopatología; en tal sentido, estudios posteriores deberán evaluar la exactitud diagnóstica de ambas pruebas (GG y PCR) frente al estándar correcto.…”
Section: Estándar: Pcr Cuantitativaunclassified
“…En estos contextos, se restringe el uso de pruebas moleculares a los casos sintomáticos con GG y prueba rápida negativas, ante resultados discordantes y en infecciones por especies diferentes a P. falciparum o P. vivax, como apoyo al control de calidad del programa de diagnóstico y para monitorear zonas de baja transmisión. Con base en los resultados de este metaanálisis, se muestra la importancia de ampliar el uso de pruebas moleculares para la vigilancia de la MAE donde se presenta una elevada frecuencia de infecciones asintomáticas y submicroscópicas (10) .…”
Section: Estándar: Pcr Cuantitativaunclassified
See 2 more Smart Citations